Medial Unicompartmental Knee Replacement Using the "Oxford Uni" Meniscal Bearing Knee - Aldinger, P; Breusch, S; Murray, D; Goodfellow, J (2003)
Medial unicompartmental knee replacement (UKR) has many advantages over total replacement (TKR) including better function and less morbidity. However, the long-term failure rates of fixed-bearing UKR are high because of polyethylene wear, lack of sophisticated instrumentation and imprecise patient selection. The fully congruent mobile bearing of the Oxford UKR exhibits minimal polyethylene wear and failure from this cause does not occur. The instrumentation allows precise implantation to restore isometric function to the ligaments. During its 20 years development, the limits of usefulness of the implant have been established and found to include about one in four knees requiring replacement for osteoarthritis. In an independent series, using these criteria, the 15 year survival was 94% (CI 86% to 100%). Since 1998, the Phase 3 implant has been used with modified instruments through a small incision, avoiding damage to the extensor mechanism. Patients now recover about three times faster than after TKR, and regain much better flexion (mean 135°). The current evidence supports that the minimally invasive Oxford UKR should be seriously considered as primary treatment and discussed with the patient presenting with anteromedial compartment osteoarthritis provided the correct indication and the appropriate surgical expertise is available.